Ras-ERK signalling represses H1.4 phosphorylation at serine 36 to promote non-small-cell lung carcinoma cells growth and migration. Issue 1 (4th December 2019) - Shi, Shaomin; Zhang, Jingzhe; Liu, Meihan; Dong, Hang; Li, Ning
Abstract: Recent papers suggest that oncogenic Ras participate in regulating tumour cells proliferation and metastasis. This work linked Ras with H1.4 modification in non-small-cell lung carcinoma (NSCLC), to better understand the oncogenic effects of Ras. A plasmid for expressing Ras mutated at G13D and T35S was transfected into NCI-H2126 and A549 cells. Phosphorylation of H1.4S36 was determined by immunoblotting. Effects of phosphorylation of H1.4 at serine (S) 36 (H1.4S36ph) on NCI-H2126 and A549 cells were tested by MTT assay, soft-agar colony formation assay, flow cytometry and transwell assay. Chromatin-immunoprecipitation (ChIP) and RT-qPCR were conducted to measure the effects of H1.4S36ph on Ras downstream genes. The catalyzing enzymes participate in H1.4S36 phosphorylation were further studied. We found that Ras-ERK signalling repressed the phosphorylation of H1.4 at S36. H1.4S36ph functioned as a tumour suppressor, as its overexpression repressed NCI-H2126 and A549 cells viability, colony formation, S-phase arrest, migration and invasion. H1.4S36ph was able to mediate the transcription of Ras downstream genes. Ras-ERK signalling repressed H1.4S36ph through degradation of PKA, and the degradation was mediated by MDM2. In conclusion, Ras-ERK signalling repressed H1.4 phosphorylation at S36 to participate in NSCLC cells growth, migration and invasion. Ras-ERK signalling repressed H1.4S36ph through MDM2-dependent degradation of PKA. This study provides a novel explanation for Ras-ERK's tumour-promoting function. Highlights: H1.4S36 phosphorylation is repressed by Ras-ERK activation; H1.4S36ph inhibits the phenotype of NSCLC cells; H1.4S36ph regulates the transcription of Ras downstream genes; Ras-ERK represses H1.4S36ph by MDM2-dependent degradation of PKA.